EMBRACING HALLYU: YOUNG INDONESIAN MUSLIMS NAVIGATING CULTURAL DIVERSITY AND RELIGIOUS IDENTITY - Kyung, Euiyoung; Binti Muhamad , Haslina; Bee Binti Mohd Hussain, Rosila (SARJANA, 2025)
ABSTRACT This study examines how young Indonesian Muslims engage with Hallyu (the Korean Wave) and its impact on their religious and cultural identities. Through qualitative fieldwork in Yogyakarta, this research reveals that participants frequently employ the term ‘modern’ to describe their engagement with Hallyu, reflecting a nuanced embrace of modernity that transcends conventional secularization paradigms. Rather than undermining religious identity, this cultural engagement is perceived as integral to their modern Muslim identity, fostering self-determination and self-realization. The findings demonstrate that Hallyu engagement facilitates dialogue between individual and collective identities within global cultural flows, illuminating the complex interplay between cultural globalization, local identities, and the modernization of Indonesian Islam. This research contributes to scholarly understanding of cultural adaptation and identity negotiation among young Muslims within Indonesia’s multicultural and religiously diverse context. Future research should examine diverse manifestations of modernity across various religious and cultural societies, moving beyond Western-centric analytical frameworks.